2006
DOI: 10.1002/0471142956.cy0623s36
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of Plasma Cells

Abstract: Plasma cell enumeration and immunophenotyping has been shown to be of value in predicting the outcome for patients with myeloma. Detection of abnormal plasma cells at a leukocyte level >0.01% at the end of therapy predicts early relapse. Although clonally related populations at varying stages of differentiation are reported to be present in myeloma, only the CD138+ fraction has been shown to directly correlate with the outcome. In addition, the plasma cell immunophenotype in monoclonal gammopathy of undetermin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…Since antibody production is crucial for the prevention of viral infections, we have shown that SCE300ET when administered along with Rb antigen, significantly enhanced the RVNA titres and the antibody titers were found to be higher as compared to Algel and rabies antigen immunized mice. CD138 is a marker for plasma cells (PCs) or antibody producing cells [25], that are differentiated from the antigen activated B cells [26]. In the present study, the increase in antibody titers was further confirmed by the increased expression of CD138 + cells in whole blood of 300ET+Rb and Algel+Rb immunized mice as compared to the inactivated Rb immunized mice.…”
Section: Discussionsupporting
confidence: 73%
“…Since antibody production is crucial for the prevention of viral infections, we have shown that SCE300ET when administered along with Rb antigen, significantly enhanced the RVNA titres and the antibody titers were found to be higher as compared to Algel and rabies antigen immunized mice. CD138 is a marker for plasma cells (PCs) or antibody producing cells [25], that are differentiated from the antigen activated B cells [26]. In the present study, the increase in antibody titers was further confirmed by the increased expression of CD138 + cells in whole blood of 300ET+Rb and Algel+Rb immunized mice as compared to the inactivated Rb immunized mice.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings suggest that ''aberrant'' immunophenotype is normal in a considerable proportion of BM PCs of healthy people. Different authors found that CD19 negative BM PCs could constitute up to 30-39% of the total BM PCs in healthy people (3,(7)(8)(9). Importantly, we showed that the majority of plasmacytes were CD19 negative in some HDs.…”
Section: Discussionmentioning
confidence: 44%
“…All samples were prepared by lysed whole blood technique to have as close cell population ratios as possible to the primary samples. Ficoll gradient cell separation and concentration procedure was not used due to possible bias in rare cell population ratios (8,10,11).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…(38) demonstrated that mice lacking XBP-1 expression in B cells could generate normal germinal center and plasma cell frequencies in response to challenge with a foreign antigen. Interestingly, they determined that XBP-1 expression occurred after B cells upregulated syndecan-1 (CD138), a receptor commonly used to identify the plasma cell population (46). As such, B220 int CD138 ϩ cell frequencies were comparable to those of littermate control mice.…”
Section: Resultsmentioning
confidence: 99%